OPTIMALISASI PELAYANAN PUBLIK SECARA ONLINE PADA KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM PROVINSI SULAWESI TENGGARA - Suriyani BB; Suci Amalya Widiastuti (Journal Publicuho, 2021)
This study aims to determine and describe optimizing public services online at the regional office of the Ministry of the Law and Human Rights in Southeast Sulawesi, this study uses descriptive qualitative methods to 5 informants determined by snowball sampling technique, data analysis techniques consist of data collection, data reduction, presentation data, drawing conclusions/verification, the data obtained were analyzed qualitatively and described in descriptive form. The results of this study indicate that public services carried out online at the regional office of the Ministry of Law and Human Rights in Southeast Sulawesi are very good, this can be seen from the implementation of services with standard operating procedures that apply during the pandemic and the handling that is in accordance with what has been determined at the regional office of the Ministry of Law and Human Rights by upholding the values of professionalism, accountability, synergy, transparency, and innovation. Based on the research, one form of research on optimizing public services is the existence of a digital-based service system that makes it easier for the public to receive services, supporting facilities, and infrastructure, as well as services provided quickly and responsively at the region of the Ministry of Law and Human Rights in Southeast Sulawesi.